The Effect of Topical Magnesium Sulfate on Dilatation, Effacement and Duration of Labor in Primiparous Women: A randomized controlled clinical trial - Ezatosadat Haji-seyed-javadi; Hamideh Pakniat; Azin Yazdani (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2024)
Introduction: Considering the excruciating process of labor as well as anxiety and fear of natural childbirth, it is necessary to find an appropriate substance for expedite progression of labor and shortening labor duration in pregnant women. This study was performed with aim to determine the effect of topical magnesium sulfate on effacement, dilatation, and labor duration in primiparous women. Methods: This randomized controlled clinical trial study was conducted in 2022 on 98 primiparous women with full-term pregnancy that had referred to Qazvin Kosar Hospital for delivery. Patients were randomly divided into intervention and control groups. After diagnosis of active phase, in the intervention group, 10 cc of magnesium sulfate 50% and in the control group, the same amount of distilled water was poured on the cervix during vaginal examination. The amount of effacement and dilatation at the beginning of the active phase and then every 2 hours, as well as mother's age, gestational age, number of pregnancies, BMI, type of delivery, duration of labor, Apgar score, weight of the baby, duration of contractions and intervals of contractions were recorded in the checklist. Data analysis was done using SPSS software (version 16) and Fisher's exact, Chi-square, t-test and Mann-Whitney tests. P<0.05 was considered statistically significant. Results: Duration and intervals of contractions in first and second examination were not significantly different in the intervention and control groups (P>0.05). Mean effacement in the intervention group at the start of active phase was 55.61±3.80 and after two hours was 70.21±4.19, which was statistically significant (P=0.021(. Mean dilatation in the intervention group at the start of active phase was 4.57±0.57 cm and two hours after was 7.31±0.71 cm, which was statistically significant (p=0.043(. Mean effacement and dilatation in the control group at the start of active phase and two hours later was not statistically significant (P>0.05). Conclusion: Topical magnesium sulfate is effective on improving dilatation and effacement during labor and help speed up delivery.